2018
DOI: 10.1117/1.nph.5.1.011019
|View full text |Cite
|
Sign up to set email alerts
|

Are ventrolateral and dorsolateral prefrontal cortices involved in the computerized Corsi block-tapping test execution? An fNIRS study

Abstract: The Corsi block-tapping test (CBT) is an old neuropsychological test that, requiring the storage and the reproduction of spatial locations, assesses spatial working memory (WM). Despite its wide use in clinical practice, the specific contribution of prefrontal cortex (PFC) subregions during CBT execution has not been clarified yet. Considering the importance of spatial WM in daily life and the well-known role of ventrolateral-PFC/dorsolateral-PFC (VLPFC/DLPFC) in WM processes, the present study was aimed at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…In fact, adapted versions of CDT were administrated during a functional Magnetic Resonance Imaging (fMRI) acquisition directly in the MRI scanner [ 14 , 15 , 16 ]. DST and CBTT were also adapted for functional neuroimaging acquisition (either through fMRI or functional Near InfraRed Spectroscopy, fNIRS) [ 15 , 16 , 17 , 18 , 19 ]. Adaptation could be related to either environmental constraints (because of the fMRI acquisition) or temporal constraints (because of the need of paced tasks that allow standard functional neuroimaging signal analysis).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, adapted versions of CDT were administrated during a functional Magnetic Resonance Imaging (fMRI) acquisition directly in the MRI scanner [ 14 , 15 , 16 ]. DST and CBTT were also adapted for functional neuroimaging acquisition (either through fMRI or functional Near InfraRed Spectroscopy, fNIRS) [ 15 , 16 , 17 , 18 , 19 ]. Adaptation could be related to either environmental constraints (because of the fMRI acquisition) or temporal constraints (because of the need of paced tasks that allow standard functional neuroimaging signal analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation could be related to either environmental constraints (because of the fMRI acquisition) or temporal constraints (because of the need of paced tasks that allow standard functional neuroimaging signal analysis). In fact, when performed with concurrent functional brain imaging, these tests are modified from a non-paced administration of tasks and free doctor-patient interaction to a block or event related paradigm where doctor is replaced by an automated stimulation (e.g., through a screen monitor or a minidisk player) [ 16 , 17 , 18 , 19 ]. Although these modifications are useful from a neuroimaging standpoint, they indeed alter the ecology of the tests and the interaction between the doctor and the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, a functional Magnetic Resonance Imaging study (fMRI) on healthy volunteers (Toepper et al 2010 ) confirmed the involvement of PFC during CBT execution. More recently, Lancia et al ( 2018 ) investigated the neural correlates of CBT by means of functional Near-Infrared Spectroscopy (fNIRS), a non-invasive neuroimaging method assessing changes in brain hemodynamics (Scholkmann et al 2014b ; Pinti et al 2018b ). As compared to the other neuroimaging techniques, the fNIRS has greater temporal resolution, lower acquisition cost, less movement-related artifacts and greater flexibility when used to study individuals in an ecological environment during natural interactions, although at the cost of lower spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to the other neuroimaging techniques, the fNIRS has greater temporal resolution, lower acquisition cost, less movement-related artifacts and greater flexibility when used to study individuals in an ecological environment during natural interactions, although at the cost of lower spatial resolution. In their study, Lancia et al ( 2018 ) specifically assessed activation of the ventrolateral and dorsolateral PFC during a computerized version of CBT and a block-suppression computerized version of the CBT, which required inhibiting a response toward distractor cubes. The results suggested that both the ventrolateral and dorsolateral PFC were involved in both tasks, without region-specific activation patterns.…”
Section: Introductionmentioning
confidence: 99%